PEMBINAAN DISIPLIN SISWA OLEH GURU DI SMK NEGERI 1 GUNUNG TULEH KABUPATEN PASAMAN BARAT - Ilham Wardi; Nelfia Adi (Universitas Negeri Padang, 2019)
The purpose of this study was to obtain information about student discipline development by teachers at SMK Negeri 1 Gunung Tuleh, West Pasaman Regency as seen from 1) student disciplinary guidance by teachers through discipline, 2) student discipline development by teachers through exemplary governance, 3) coaching student discipline by the teacher through guidance, 4) student discipline development by the teacher through punishment, 5) student discipline development by the teacher through supervision.This study was a descriptive study. The total population in this study was 236 people. Samples were taken with Simple Random Samplingtechniquewith 70 people. The data collection tool used is a Likert scale model questionnaire with 5 alternative answers Questionnaires have been tested for validity and reliability. Data were analyzed using the average formula.The results of the study show that: 1) student discipline development by teachers through discipline is stated to be good with an average score of 3.69, 2) student discipline development by teachers through exemplary governance is stated to be quite good with an average score of 3.52, 3) student disciplinary guidance by the teacher through guidance expressed either with an average score of 3.65, 4) student discipline development by the teacher through punishment expressed both with an average score of 3.75, 5) student discipline development by the teacher through supervision expressed well with an average score 3.75. Overall, Student Discipline Development by Teachers at SMK Negeri 1 Gunung Tuleh, West Pasaman Regency is 3, 76 in the good category. This indicates that the discipline of student discipline by teachers at SMK Negeri 1 Gunung Tuleh, West Pasaman Regency is good, but it still needs to be maintained and improved again so that it increases in the excellent category.